Subcortical Hypermetabolism Associated With Cortical Hypometabolism Is a Common Metabolic Pattern in Patients With Anti-Leucine-Rich Glioma-Inactivated 1 Antibody Encephalitis - Zhao, Xiaobin; Zhao, Shaokun; Chen, Yaojing; Zhang, Zhanjun; Li, Xiaotong; Liu, Xiao; Lv, Ruijuan; Wang, Qun; Ai, Lin (Frontiers in Immunology, 2021)
Purpose Brain 18F-fluorodeoxyglucose positron emission tomography (FDG PET) is a sensitive technique for assisting in the diagnosis of patients with anti-leucine-rich glioma-inactivated 1 (LGI1) antibody encephalitis. However, the common pattern of this disorder assessed by FDG PET remains unknown. The present study aimed to explore the glucose metabolic patterns of this disorder based on PET voxel analysis. Methods This retrospective study enrolled 25 patients with anti-LGI1 encephalitis, who were admitted in Beijing Tiantan Hospital between September 2014 and July 2019. The glucose metabolic pattern was compared between the included patients and 44 age- and gender-matched healthy controls using Statistical Parametric Mapping. Then, the correlation between the metabolic pattern and scaled activities of daily living (ADLs) of the patients was assessed. Results The median time from symptom onset to PET scans was 9 w (range :2-53w). The groupwise analysis revealed that patients with anti-LGI1 encephalitis had left hippocampal hypermetabolism and hypometabolism in almost all neocortical regions. The individual-level results showed most patients presented a decreased metabolism in neocortical regions, as well as an increase in metabolism in the hippocampus and basal ganglia. Furthermore, the metabolic gradient between hippocampus and neocortical regions was positively associated with the ADLs (frontal lobe, r=0.529, P=0.008; parietal lobe, r=0.474, P=0.019; occipital lobe, r=0.413, P=0.045; temporal lobe, r=0.490, P=0.015), respectively. In addition, the patients with facio-brachial dystonic seizures (FBDS) presented bilateral putamen hypermetabolism, when compared to patients without FBDS and healthy controls. Conclusion Subcortical hypermetabolism associated with cortical hypometabolism presented with a common metabolic pattern in patients with anti-LGI1 encephalitis in the present study. The resolution of the metabolic gradient of the hippocampal hypermetabolism and neocortical hypometabolism may bring about improved clinical neurologic disability.